#TITLE_ALTERNATIVE# - HADI SUBROTO WILOKISWORO (NIM 13703023), RADEN
Sintering is the important process in the making of porcelain body tile, because it makes the product stronger, less in porosity, and has shrinkage. Shrinkage in porcelain body tile is mass transport which need controlling in order to maintain the uniform dimension of product. By knowing the mass transport mechanism of porcelain body tile during sintering, the controlling of linear shrinkage can be done perfectly. In this research, Na-feldspar and K-feldspar are used to make the porcelain body tile. The making of porcelain body tile is started with powder preparation which continued with powder press using uniaxial pressing machine. After pressing, green body is dried in the oven, then fired with variation of sintering temperature (1050oC, 1100oC, 1150oC, and 1200oC) and sintering time (60 minute, 90 minute, dan 120 minute). After it is fired in the kiln, the next step is measure the linear shrinkage of porcelain body tile by using digital caliper. The contents of linear shrinkage analysis are the comparison of linear shrinkage between Na-porcelain body tile and K-porcelain body tile; The kind of mass transport mechanism of porcelain body tile during sintering; The effect of sintering temperature and sintering time to linear shrinkage of porcelain body tile. The research inform that the loss on ignition of porcelain body tile during sintering is about (6-8%). The maximum value of linear shrinkage is 8%. By the increasing number of feldspar composition, sintering temperature, and sintering time, the linear shrinkage of porcelain body tile is also increase. Linear shrinkage of K-porcelain body tile is higher than Na-porcelain body tile at the similar feldspar composition, sintering temperature, and sintering time. Mass transport mechanism that happens on Naporcelain body tile are evaporation-condensation, surface diffusion, and lattice diffusion on grain boundary. Mass transport mechanism that happens on K-porcelain body tile are evaporation-condensation, grain boundary diffusion, and lattice diffusion on grain boundary.